Employee Engagement Mediates The HR PracticesPerformance Relationship in ITES: A Quantitative Study - M, Sangeetha; K, Dr. Vijayaraj (International Journal of Accounting and Economics Studies, 2025)
This study uses PLS-SEM analysis to examine how employee engagement mediates the link between HR practices and organizational ‎performance in the Indian ITES industry. A standardized questionnaire measuring corporate performance, employee engagement, and ‎HR procedures was used to gather data from 300 ITES experts. The findings show that employee engagement has a high impact on ‎organizational success (β = 0.580), whereas HR practices have a lesser but beneficial direct effect on organizational performance (β = ‎‎0.164). With a substantial indirect impact (B = 0.3017) in the –HR-performance link, mediation analysis validates the partial mediating ‎function of employee engagement. With intermediate explanatory power, the model was able to explain 43.5% of the variance in organizational performance and 14.3% of the variance in employee engagement. The results highlight how good HR procedures increase em-‎employee engagement, which significantly enhances organizational results and is consistent with social exchange theory. In addition to ‎offering HR managers useful advice on how to create engagement-centric HR strategies to boost organizational competitiveness in the ‎dynamic ITES sector, this study adds empirical support for the HR–engagement–performance route to the body of knowledge in HRM‎.
Keywords: Employee Engagement; HR Practices; Organizational Performance; Mediation Analysis; ITES Industry